2018
DOI: 10.1016/j.celrep.2017.12.029
|View full text |Cite
|
Sign up to set email alerts
|

The Apolipoprotein M/S1P Axis Controls Triglyceride Metabolism and Brown Fat Activity

Abstract: Apolipoprotein M (apoM) is the carrier of sphingosine-1-phosphate (S1P) in plasma high-density lipoproteins. S1P is a bioactive lipid interacting with five receptors (S1P). We show that lack of apoM in mice increases the amount of brown adipose tissue (BAT), accelerates the clearance of postprandial triglycerides, and protects against diet-induced obesity (i.e., a phenotype similar to that induced by cold exposure or β-adrenergic stimulation). Moreover, the data suggest that the phenotype of apoM-deficient mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 61 publications
2
42
1
Order By: Relevance
“…In addition, it was shown that ApoM deficiency protects against diet-induced obesity and improves glucose tolerance. However, in the present study, female ApoM-knockout mice were used 4 . Previous studies have shown that estrogen upregulates the expression of ApoM through estrogen receptor a 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was shown that ApoM deficiency protects against diet-induced obesity and improves glucose tolerance. However, in the present study, female ApoM-knockout mice were used 4 . Previous studies have shown that estrogen upregulates the expression of ApoM through estrogen receptor a 20 .…”
Section: Discussionmentioning
confidence: 99%
“…HDL in type 2 diabetes patients loses the ability to maintain proper endothelial function, possibly as a result of the loss of S1P, and might contribute to the development of diabetic complications 3 . Christoffersen et al 4 showed that ApoM deficiency protects against diet-induced obesity and improves glucose tolerance. Furthermore, we reported that plasma ApoM was decreased by 70% in diabetic mice, ApoM messenger ribonucleic acid (mRNA) levels in the liver were decreased by 40%, and ApoM mRNA levels in the liver and kidneys were increased by the injection of exogenous insulin 5 .…”
Section: Introductionmentioning
confidence: 99%
“…A recentstudy demonstrated that lack of ApoM in mice increases the amount of brown adipose tissue (BAT), accelerates clearance of postprandial triglycerides, and protects against diet-induced obesity. Moreover, ApoM-de cient mice phenotype is S1Pdependent and re ects diminished S1P1 stimulation [22]. In genetically modi ed mice, changes in plasma ApoM concentration resulted in quantitative and qualitative changes in HDLs, while its overexpression reduced atherosclerosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Together with the novel data in this manuscript, these findings suggest that there are at least two independent mechanisms by which hepatic FoxOs regulate HDL composition. S1P is a signaling molecule, and it is been reported that S1P can induce differential effects, depending on its chaperone, either ApoM or albumin 16,[20][21][22][23] . The molecular mechanisms for the differential effects between ApoM-and albumin-bound S1P remain under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In plasma, around 65% of S1P is carried by HDL-bound ApoM and the remainder is found in the lipoprotein depleted (LPD) fraction, presumably associated to albumin 16,19 . Importantly, S1P induces differential effects depending on whether it is associated with ApoM or albumin 20,21 . This is exemplified by the ability of the HDL-ApoM-S1P complex to enhance endothelial function 16,[22][23][24] .…”
Section: Introductionmentioning
confidence: 99%